Implementasi TOPSIS Pada Sistem Rekomendasi Tempat Latihan Bela Diri Di Kota Malang Berbasis Lokasi - Ade Armawi Paypas; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
There are various types of martial arts that exist in the world, including silat from Indonesia, kung fu from China, and karate from Japan. Because of the many types of martial arts, with the growing age, more and more martial arts training centers are scattered throughout the world. But with so many martial arts places, sometimes people don't know which is better. With this application, users can get recommendations for martial arts training sites based on GPS-based locations. The recommendation system for the place of self-defense training is designed using the TOPSIS method with data criteria in the form of distance between users and practice sites, training costs in 1 month, and the amount of training time in 1 week, and implemented on the android platform. The results of this blackbox test show that 100% of the functionality is valid. Other tests carried out are testing the validation of algorithms, where testing is done by comparing the results of the system with manual calculations. The results of system calculations and manual calculations are 100% the same, and rank consistency testing, where testing is carried out to determine the consistency of the recommendations when the number of criteria is added or reduced. The rank consistency test results show that the ranking results are consistent when the criteria are added, and will change when the number of criteria is reduced.